Association between caries experience and reproductive history of women; a population-based study - Roya Safari Faramani; Narges Ziaei; Farid Najafi; Mahsa Miryan; Mitra Darbandi (BMC Oral Health)
Abstract Background The underlying cause of poor oral health in women of reproductive age remains unclear. This study aimed to explore the association between caries experience and reproductive history, focusing on age at menarche, age at menopause, and number of pregnancies. Methods This cross-sectional study analyzed women from the baseline phase of the Ravansar Non-Communicable Disease (RaNCD) cohort. Data on reproductive history, including age at menarche, number of pregnancies, age at first pregnancy, and breastfeeding duration, were collected via questionnaire. The Decayed, Missing, and Filled Teeth (DMFT) index was assessed using dental examinations conducted with standard instruments. Reproductive history was considered the exposure variable, while caries experience was the outcome. Statistical analyses, including t-tests, One-way ANOVA, and linear regression, were conducted to examine associations between reproductive history and oral health. Results A total of 5,151 women were assessed, with a mean age of 47.56 ± 8.46 years. Of these 42.46% lived in rural areas. The mean DMFT score in the overall population was 16.47 ± 9.19. Women who used dental floss had a significantly lower median DMFT than those who did not (16 vs. 12, P < 0.001). In the adjusted model, DMFT increased significantly by 0.30 for each additional pregnancy (β = 0.30,95%CI:0.04,0.56). However, no significant associations were observed between age at menstruation, frequency of abortion, age at first pregnancy, or age at menopause and DMFT. Conclusions The findings indicate that the number of pregnancies is significantly associated with caries experience. Further, longitudinal studies are needed to replicate this study findings.